1992
DOI: 10.1902/jop.1992.63.11.859
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implants: A Review

Abstract: The present article is a review presenting an update on the field of dental implants since the World Workshop in Clinical Periodontics in July 1989. Areas that are discussed include following: 1. Biomaterials and the implant interface, and the interaction of these with the environment. 2. Periodontal considerations including data supporting a perimucosal seal of implant to soft tissue and discussion of the endosseous interface between the bone and the implant. 3. Newer techniques of diagnostic imaging and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
15

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 24 publications
1
69
0
15
Order By: Relevance
“…Biochemical changes in the peri-implant environment may lead to implant corrosion (Laing, 1973). Thus, titanium implant corrosion is affected not only by the concentration of electrolytes but also by saliva pH (Duffó et al, 1999;Nikolopoulou, 2006) which can vary in areas around dental implants (Meffert et al, 1992). Lotthar et al (1992) reported that titanium does not withstand a large number of chemical substances.…”
Section: Clinical Implications Of Corrosionmentioning
confidence: 99%
“…Biochemical changes in the peri-implant environment may lead to implant corrosion (Laing, 1973). Thus, titanium implant corrosion is affected not only by the concentration of electrolytes but also by saliva pH (Duffó et al, 1999;Nikolopoulou, 2006) which can vary in areas around dental implants (Meffert et al, 1992). Lotthar et al (1992) reported that titanium does not withstand a large number of chemical substances.…”
Section: Clinical Implications Of Corrosionmentioning
confidence: 99%
“…Either of these situations can lead to detrimental consequences. [15] Home care for dental implant-supported restorations similar to traditional oral hygiene procedures, with some minor modifications are as follows.…”
Section: Fig 2: Hawe Implant Pastementioning
confidence: 99%
“…[20][21][22] Variations in the anatomic structure of different jaw regions and/or inadvertent oversizing of the implant site may result in an implant that is slightly mobile. 23 Orenstein et al 24 reported that implant mobility at placement may present a serious risk to successful integration at uncovering and to long-term survival of some implant types.…”
Section: Clinical Studiesmentioning
confidence: 99%